1992
DOI: 10.1111/j.1365-2311.1992.tb01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric larval competition between two species of solitary parasitoid wasps: the influence of superparasitism

Abstract: Abstract. We test the hypothesis that a solitary parasitoid wasp may gain in fitness if she lays more eggs in a host. Using heterospecific superparasitism (=multiparasitism) between the solitary aphid parasitoids, Aphidius smithi Sharma & Subba Rao and Ephedrus californicus Baker, we show that (i) a superparasitizing female's chance that her offspring will survive competition is an increasing function of egg density, and (ii) survival among same‐aged larvae is independent of the oviposition sequence. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…This investment in time and effort will be lost if a mummy is rejected or, if accepted, offspring do not survive. However, a female can gain fi tness by depositing more than one egg per host if the probability of one of her own offspring surviving larval competition increases with clutch size (Visser et al, , 1992Mackauer et al, 1992). Moreover, Mackauer & Chow (2015) found that larvae of D. carpenteri are facultatively gregarious, with two and occasionally three offspring successfully developing on a superparasitized host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This investment in time and effort will be lost if a mummy is rejected or, if accepted, offspring do not survive. However, a female can gain fi tness by depositing more than one egg per host if the probability of one of her own offspring surviving larval competition increases with clutch size (Visser et al, , 1992Mackauer et al, 1992). Moreover, Mackauer & Chow (2015) found that larvae of D. carpenteri are facultatively gregarious, with two and occasionally three offspring successfully developing on a superparasitized host.…”
Section: Discussionmentioning
confidence: 99%
“…Host quality is not absolute but relative, depending on the kinds of host available and the female's physiological state (van den Assem, 1971;Cloutier et al, 1991;Mackauer et al, 1996). Having encountered an already parasitized host, a female may place a higher value on the next host she fi nds, regardless of its quality, and deposit a fertilized egg (van den Assem, 1971;Cloutier et al, 1991) or superparasitize it if her offspring is likely to survive larval competition (Mackauer et al, 1992;Visser et al, 1990Visser et al, , 1992Lebreton et al, 2009). Increased superparasitism can also be induced by pre-experiment experience, for example, when females are kept in groups .…”
Section: Introductionmentioning
confidence: 99%
“…size, sex, age, previous parasitism), adult population sex ratio, competition with other foragers, seasonal changes in temperature, photoperiod and humidity (King 1987;Godfray 1994). Furthermore, beyond the mother's decision, sex ratio can also be explained as the result of sperm reserve depletion or virginity (King 1987;Godfray 1990), larval developmental mortality (Wellings et al 1986;Hardy et al 1998), physical (Mackauer et al 1992;NØnon et al 1995;van Baaren et al 1997) or physiological suppression due to superparasitism (Vinson 1980;Vinson and Hegazi 1998), Wolbachia infection (Stouthamer et al 2002), ovicide (Antolin et al 1995), hyperparasitism (Heinz 1996) or encapsulation (van Alphen and Visser 1990;Strand and Pech 1995). Therefore, we should distinguish between primary sex ratio (before any mortality factor occurs) and secondary sex ratio (after all mortality factors have acted) (Godfray 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although we often observe multiple ovipositions in the laboratory (our unpublished data), no studies have investigated intraspecific larval competition and superparasitism-avoidance behavior in M. pulchricornis. There are two types of intraspecific competition in superparasitism; i.e., symmetrical competition between individuals of approximately the same age (Mackauer, 1990;Mackauer et al, 1992) and asymmetrical competition between individuals of different ages. Competition may occur via physical attacks using the sharp mandibles (Salt, 1961;Mackauer, 1984, 1986) or via physiological suppression caused by toxicity, nutrient removal, or asphyxiation (Fisher, 1961(Fisher, , 1971Vinson and Iwantsch, 1980;Vinson and Hegazi, 1998).…”
Section: Introductionmentioning
confidence: 99%